Factory Relocation of Global Manufacturing Enterprises: A Case Study - Leu, Jun-Der; Huang, Yu-Tsung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
A manufacturing enterprise undertakes factory relocation to enhance growth and development or to solve financial or operational problems. This strategic decision has an impact on long-term profitability so that a factory relocation reference model as decision support is required. In this research, we propose a reference model for the factory relocation of global manufacturing enterprises. The reference model includes the phases of industrial background analysis, relocation plan and execution, and performance evaluation. The reference model is applied to a global electronics manufacturing company. The implementation of the case is described, and the performance of profitability and productivity is analyzed using nine years of business historical data. Experiences gleaned in this case study can be used as a reference for global manufacturing enterprises.